A Comparative Study of Polycrystal/Single‐Crystal LiNi0.8Co0.1Mn0.1O2 in All‐Solid‐State Li‐Ion Batteries with Halide‐Based Electrolyte under Low Stacking Pressure. Issue 4 (17th February 2023) - Liu, Hao-Wen; Parthasarathi, Senthil-Kumar; Thi, Shiki; Weng, Yu-Ting; Bolloju, Satish; Chen, Chia-Chin; Jeng, Ru-Jong; Wu, Nae-Lih
Abstract : Composite cathodes consisting of a LiNi0.8 Co0.1 Mn0.1 O2 (NCM) cathode and brittle Li3 InCl6 (LIC) solid‐state electrolyte (SSE) are assessed for all‐solid‐state Li‐ion battery (ASSLIB) applications under a low stacking pressure (coin‐cell configuration: ≈2.0 MPa). Herein, an investigation is conducted to understand how the internal particle morphologies of the polycrystal (PC‐)/single‐crystal (SC‐) NCM cathode materials affect the internal cracking within the composite electrodes and thereby electrode performance. Extensive debonding between NCM and LIC takes place even at a very low current density (0.03C) with high voltage (4.4 V), but substantially narrower/shorter debonding gaps are observed for SC‐NCM as compared with PC‐NCM (wider/lengthier) due to their different particle sizes. High current rates (e.g., 0.1C) bring about greater strain rates in PC‐NCM particles, resulting in widespread microcracking along the grain boundaries between primary particles and consequently creating "dead zones" that are isolated from the ionic and electronic conduction pathways. Although SC‐NCM shows microcracking within the agglomerates, individual NCM crystals remain in close contact with the SSEs because of noticeably fewer grains in the agglomerations than in the PC‐NCM secondary particles. A low‐pressure SC‐NCM ASSLIB is demonstrated with good cycle stability comparable with that of a liquid‐electrolyte cell even under stressful currents. Abstract : An in‐depth investigation of the electrochemical performance and cracking mechanism of single‐crystal (SC) and polycrystal (PC) NCM811 in all‐solid‐state Li‐ion batteries under a low compression pressure of 2 MPa is conducted. Under both high‐voltage and high‐current protocols, SC‐NCM811 experiences a lower degree of cracking and debonding than PC‐NCM811 cells, eventually exhibiting superior cycle stability.